2022
DOI: 10.1007/s40558-022-00233-w
|View full text |Cite
|
Sign up to set email alerts
|

How does celebrity involvement influence travel intention? The case of promoting Chengdu on TikTok

Abstract: This study examines the predicting effect of celebrity involvement on destination authenticity (object-based authenticity and existential authenticity) and hence travel intention in the context of TikTok tourism promotional videos. Data collected from 225 survey respondents indicated that celebrity involvement increases perceived destination authenticities (object-based and existential authenticity) and hence travel intention after watching TikTok celebrity videos. Furthermore, destination authenticities media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…arrests) news (e.g. tax evasion) (Zhu et al, 2022a(Zhu et al, , 2022b, some scholars have shown that social media influencers can be an effective marketing strategy for enhancing destination marketing (Chen et al, 2020;Pop et al, 2022). However, how is this attachment to social media influencers formed on TikTok and how does it shape behavioral intention?…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…arrests) news (e.g. tax evasion) (Zhu et al, 2022a(Zhu et al, , 2022b, some scholars have shown that social media influencers can be an effective marketing strategy for enhancing destination marketing (Chen et al, 2020;Pop et al, 2022). However, how is this attachment to social media influencers formed on TikTok and how does it shape behavioral intention?…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, Kim and Kim (2020) have shown that authenticity is an important antecedent that engages potential consumers in social media tourism. Although Zhu et al (2022b) claimed authenticity as a psychological mechanism to explore how it is shaped in social media and how it affects customer behavior in social media, they ignored that authenticity can also act as a stimulus to influence consumer psychology and behavior based on TikTok.…”
Section: Mediating Role Of Attachmentmentioning
confidence: 99%
See 3 more Smart Citations